2017
DOI: 10.3747/co.24.3704
|View full text |Cite
|
Sign up to set email alerts
|

Acute Care Hospitalization Near the End of Life for Cancer Patients Who Die in Hospital in Canada

Abstract: Acute care hospitals have a role in managing the health care needs of people affected by cancer when they are at the end of life. However, there is a need to provide end-of-life care in other settings, including at home or in hospice, when such settings are more appropriate. Using data from 9 provinces, we examined indicators that describe the current landscape of acute care hospital use at the end of life for patients who died of cancer in hospital in Canada.Interprovincial variation was observed in acute car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 14 publications
0
12
1
Order By: Relevance
“…However, 90.4% of the matched control group had at least 1 palliative consultation code, slightly less than the 93.1% in the Symptom Management Program group. Also, our estimates of death in an acute care hospital and use of any aggressive endof-life care in the control group were only marginally higher than Ontario provincial estimates derived with these same administrative sources but using a decedent cancer cohort definition (44% v. 40% for death in an acute care hospital 21 and 25% v. 22.5% for aggressive end-of-life care). Conversely, if members of the control group received comprehensive hospice palliative care through a family physician or group health team, our outcome estimates may be conservative.…”
Section: Limitationscontrasting
confidence: 65%
See 2 more Smart Citations
“…However, 90.4% of the matched control group had at least 1 palliative consultation code, slightly less than the 93.1% in the Symptom Management Program group. Also, our estimates of death in an acute care hospital and use of any aggressive endof-life care in the control group were only marginally higher than Ontario provincial estimates derived with these same administrative sources but using a decedent cancer cohort definition (44% v. 40% for death in an acute care hospital 21 and 25% v. 22.5% for aggressive end-of-life care). Conversely, if members of the control group received comprehensive hospice palliative care through a family physician or group health team, our outcome estimates may be conservative.…”
Section: Limitationscontrasting
confidence: 65%
“…Wodchis and colleagues 6 showed that palliative care is one of the most common reasons for hospital admission among high-cost users in Ontario, and Cheung and colleagues 5 reported that patients with cancer in Ontario who OPEN Research received aggressive end-of-life care incurred costs that were 43% higher than those for patients managed nonaggressively. Although admission to an acute care hospital may be appropriate for patients with cancer because of disease progression or a need for optimal treatment 21 or caregiver respite, overuse may signal a potential gap in palliative care services. 21,22 The risk difference of almost 20% in our study suggests that enrolment in the Symptom Management Program may be associ-ated with allowing for death to occur outside the acute care hospital setting for patients with cancer in the Sudbury region.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because many of these important aspects of care are difficult to measure directly, we used encounters with acute care services as a proxy. This is a reasonable surrogate marker since patients typically present urgently to medical attention when symptoms are poorly managed, when supports at home are inadequate, or when end‐of‐life care needs are not sufficiently addressed . In our analysis, we found that nonreferred patients are more likely to use specific acute care services, such as hospitalizations, when compared to referred patients.…”
Section: Discussionmentioning
confidence: 80%
“…We did not differentiate multiple visits within hospital costs; nonetheless, even among cancer patients who die in hospital in Ontario, the majority (77%) only have a single visit in the last month. 31 Because we used a matched-pair analysis at the individual pair level (and pairs are chosen from within the same or similar regions), we did not account for clustering within teams. Our post hoc sensitivity analysis, however, weighted by team, produced results that were similar in value and in level of significance.…”
Section: Research Limitationsmentioning
confidence: 99%